2016
DOI: 10.5424/fs/2016253-08610
|View full text |Cite
|
Sign up to set email alerts
|

Growth decline assessment in Pinus sylvestris L. and Pinus nigra Arnold. forest by using 3-PG model.

Abstract: Aim of the study : We assessed the ability of the 3-PG process-based model to accurately predict growth of Pinus sylvestris and P. nigra plantations across a range of sites, showing declining growth trends, in southern Spain.Area of study: The study area is located in "Sierra de Los Filabres" (Almería). Material and methods:The model was modified in fifteen parameters to predict diameter (DBH, cm), basal area increment (BAI, cm 2 yr -1 ) and leaf area index (LAI, m 2 m -2 ) in healthy trees and trees showing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 47 publications
1
4
0
1
Order By: Relevance
“…In homogeneous canopies such as those of pine plantations, higher LAI values are expected for healthy vegetation. These results are consistent with other studies in P. sylvestris plantations under Mediterranean conditions [66]; although, a significant reduction in leaf area may be expected due to defoliation [20].…”
Section: Tree Crown Biochemical Variables At the Plot Levelsupporting
confidence: 93%
“…In homogeneous canopies such as those of pine plantations, higher LAI values are expected for healthy vegetation. These results are consistent with other studies in P. sylvestris plantations under Mediterranean conditions [66]; although, a significant reduction in leaf area may be expected due to defoliation [20].…”
Section: Tree Crown Biochemical Variables At the Plot Levelsupporting
confidence: 93%
“…The results of this research are very different from those of the other related studies in forest decline (Temiño-Villota et al 2016;Navarro-Cerrillo et al 2016) because of using the managerial and mathematical methods and the previous forest decline models (Kabrick et al 2008;Ríos-Saldaña et al 2018). Compared to the previous forestry model studies, this study has targeted a different field of study in forest management.…”
Section: Resultsmentioning
confidence: 69%
“…alphaCx, pFS20, gammaF1), and minimal to parameters to which 3-PG outputs are relatively insensitive (e.g. Tmax, CoeffCond, Max-Intcptn) (for 3-PG sensitivity analyses, see Almeida et al 2004;Esprey et al 2004;Forrester and Tang 2016;Law et al 2000;Mathys et al 2014;Meyer et al 2017;Navarro-Cerrillo et al 2016;Pérez-Cruzado et al 2011;Potithep and Yasuoka 2011;Xenakis et al 2008). The largest reduction in uncertainty for all species was for parameters associated with biomass partitioning (pFS20), root or foliage litterfall (gammaF1, gammaR) and light-use efficiency (alphaCx).…”
Section: Discussionmentioning
confidence: 99%
“…Bayesian inference was used to derive parameter estimates and uncertainties for 18 parameters (Table 2). These 18 parameters were selected because they could not be calculated directly from our data, such as those in step 1, and sensitivity analyses have shown that 3-PG is sensitive to these parameters (Almeida et al 2004;Esprey et al 2004;Forrester and Tang 2016;Law et al 2000;Mathys et al 2014;Meyer et al 2017;Navarro-Cerrillo et al 2016;Pérez-Cruzado et al 2011;Potithep and Yasuoka 2011;Xenakis et al 2008). This step was based on 161 EFM and 152 NFI plots.…”
Section: Step 2-bayesian Calibrationmentioning
confidence: 99%